Legal ethics and the lawyer-client relationship in South Africa: a proposal for reform using local values - Kruuse, Helen Julia (Rhodes University, Faculty of Law, Law)
This thesis develops an approach to ethical decision-making for legal practitioners in South Africa that, it is argued, meets the ends and values of its relatively new constitutional democracy. The thesis starts by identifying that neutral partisanship was, and continues to be, the prevailing conception of role for legal practitioners in South Africa. The study focuses on how this approach is problematic for a number of reasons, the most important of which are: (1) because neutral partisanship allows lawyers to become ethically disengaged, and (2) the approach does not fit with the values of South Africa's Constitution. The study proceeds to consider alternatives to the neutral partisanship model, analysing their underlying premises and 'fit' with the South African context. The study argues that the work of William Simon, a US scholar, is the most suitable approach to adopt in South Africa. This is because of its emphasis on the need for legal practitioners to exercise discretion in ethical decision-making, to take responsibility for their actions, and ultimately to seek justice as understood within the legal system in which they operate. The study then shifts to a consideration of how Simon's approach needs to be contextualised given that it has been developed from a western/Global North perspective. To do this, I consider the content of the indigenous value of Ubuntu and its incorporation into the South African legal system. I then consider how Ubuntu could assist in the development of legal practitioners' understanding, purpose and execution of their duties within a transformative constitutional democracy. In doing this, I develop inward- and outward-looking factors based on traditional and constitutional values directing legal practitioners in their ethical decision-making. Finally, the study closes with a consideration of how the approach can be institutionalised. The study proposes certain ways in which code regulation and education can support the success of the approach.
Keywords: Legal ethics; Lawyers -- South Africa; Attorney and client -- South Africa; Ubuntu (Philosophy); Constitutionalism; Justice; Decision making